Anti-collision zone division based hazard avoidance guidance for asteroid landing with constant thrust. (January 2022) - Zhu, Shengying; Yang, He; Cui, Pingyuan; Xu, Rui; Liang, Zixuan
Abstract: Future asteroid landing and sample return missions will seek for landing sites with high scientific value, such as hazardous terrains, which means that the spacecraft needs the ability of autonomous hazard avoidance. Nowadays, the guidance algorithm based on artificial potential function plays an increasingly important role in hazard avoidance, but the local minimum problem makes that the spacecraft cannot reach the desired target landing point in some complex terrains. In this paper, a novel hazard avoidance guidance method which improves the traditional artificial potential function is developed. This method focuses on the impact zone analysis of hazards and defines anti-collision zone. In addition, a new repulsive potential function in logarithmic form is designed with continuity and fast numerical change rate in the anti-collision zone on this basis, and the problem of spacecraft falling into local minimum zone in complex terrains can be effectively avoided. Considering the practical application of constant thrust engine, the hazard avoidance control law with constant thrust sliding mode is designed to reduce switching frequency and fuel consumption. The performance of the proposed guidance law is verified through a set of simulations, as well as the global stability of the control system under uncertainty and perturbation conditions. Highlights: A novel hazard avoidance guidance for asteroid landing with constant thrust is proposed. The concept of anti-collision zone is presented based on the impact zone analysis of hazards. A new potential function in logarithmic form is established to avoid local minimum problem. The constant thrust sliding mode control law is developed to reduce fuel consumption.